Komunikasi Partisipatif dan Produksi Kreatif Bank Sampah Anggrek dalam Komunikasi Lingkungan Mitigasi Banjir di Ciliwung - Wulandari, Dhesi Kusuma; M. Fikri Akbar; Sandy Allifiansyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the practice of participatory communication and creative production implemented by the Anggrek Waste Bank along the Ciliwung River as an educational strategy for flood disaster mitigation. The research aims to understand how community-based waste management initiatives can serve as platforms for environmental learning and social empowerment. Using a qualitative approach with a case study method, this study investigates social dynamics, interaction patterns, and meanings constructed by residents through collaborative waste management and creative production activities. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that participatory communication is manifested not only in formal education, counseling, or campaigns, but also in everyday interactions, creative workshops, and collective community work. Creative products such as recycled crafts, soap made from used cooking oil, and eco enzymes function as symbolic communication media that persuasively convey ecological messages while providing tangible economic benefits. These practices foster a sense of ecological responsibility, strengthen social solidarity, and enhance community resilience to flooding. This study concludes that participatory communication integrated with creative production serves as an effective model for promoting sustainable behavior and community-based flood mitigation in urban environments.